Evolution after Gene Duplication. - Dittmar, Katharina (Wiley, 2011)
Gene duplication has long been believed to have played a major role in the rise of biological novelty through evolution of new function and gene expression patterns. The first book to examine gene duplication across all levels of biological organization, Evolution after Gene Duplication presents a comprehensive picture of the mechanistic process by which gene duplication may have played a role in generating biodiversity. Key Features:Explores comparative genomics, genome evolution studies and analysis of multi-gene families such as Hox, globins, olfactory.